Family Christmas at Frances Kamp's San Mateo Home - Watkins, Howard::::::::: (1984)
Frances Kamp with arms around Adam Watkins, Gail Graham, Christine Watkins, Jackie Hijmans, Cary Hijmans with Greg Graham, Richard Graham, Howard Watkins, Jerry Kamp in front yard